2009
DOI: 10.1007/s11805-009-0042-x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly methylated MGMT, hMLH1 and hMSH2 in tumor and serum DNA of gliomas patients

Abstract: OBJECTIVEThis study is to investigate the prevalence of promoter CpG island methylation of O 6 -methylguananine-DNA methyltransferase (MGMT), mismatch repair genes (hMLH1 and hMSH2) in both tumor and serum samples of gliomas. METHODS Methylation-specifi c PCR (MSP) was employed to detect promoter CpG island methylation of the MGMT, hMLH1 and hMSH2 genes in 39 samples taken from surgery and 32 samples of pretreatment serum all from the patients with gliomas. RESULTS Promoter CpG island methylation of MGMT, hMLH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Ali-Osman et al [15] detected 97 CpG methylation sites at Fas gene promoter region in 46 cases of HCC tissues and found that methylated CpG sites in the tumor cells of negative Fas expression were more than those in tumor cells of positive Fas expression and normal cells. Some reported that in Fas gene promoter of gliomas the rate of methylation was 46.2%, while almost no methylation was detected in normal control, indicating that Fas promoter methylation may be the early molecular events in gliomas [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Ali-Osman et al [15] detected 97 CpG methylation sites at Fas gene promoter region in 46 cases of HCC tissues and found that methylated CpG sites in the tumor cells of negative Fas expression were more than those in tumor cells of positive Fas expression and normal cells. Some reported that in Fas gene promoter of gliomas the rate of methylation was 46.2%, while almost no methylation was detected in normal control, indicating that Fas promoter methylation may be the early molecular events in gliomas [16] .…”
Section: Discussionmentioning
confidence: 99%